Strategi Pengoptimalan Performansi Kerja Berdasarkan Human Reliability Akibat Laju Beban Kerja Mental Pada Pegawai Fakultas Teknik Industri Perguruan Tinggi XYZ - PUTRA, DHIAZ ILYASA (e-Proceeding FTI, 2024)
The job of a faculty employee is an administrative job that is dominated by mental work, which relies on cognitive abilities. This study will examine the relationship between the rate of mental workload and human reliability in administrative workers. The workload rate is seen from HRV and human reliability seen from errors that occur in measuring cognitive performance through the stroop test. The results showed that there was no relationship between the rate of mental workload and human reliability or cognitive performance in Perguruan Tinggi XYZ Industrial Engineering Faculty employees. This is because the cognitive load received during the stroop test is not a difficult task and there is no excessive mental effort that can trigger mental fatigue and impact on performance. There is a decrease in human reliability towards the end of working hours and the average mean time to human error of all participants is, 155.7 minutes (2.59 hours). Thus, a strategy to optimize performance means that employees need to rest after 2.59 hours of work. Abstrak Pekerjaan pegawai fakultas adalah pekerjaan administrasi yang didominasi oleh kerja mental, yang mengandalkan kemampuan kognitif. Penelitian ini akan mengkaji hubungan laju beban kerja mental dan human reliability pada pekerja adminsitrasi.Laju beban kerja dilihat dari HRV dan human reliability dilihat dari kesalahan yang terjadi pada pengukuran performansi kognitif melalui stroop test. Hasil penelitian menunjukkan bahwa tidak terdapat hubungan antara laju beban kerja mental dengan human reliability maupun performansi kognitif pada pegawai Fakultas Teknik Industri Perguruan Tinggi XYZ. Hal ini disebabkan beban kognitif yang diterima selama pengujian stroop test bukan tugas yang sulit dan tidak terjadi mental effort yang berlebihan yang dapat memicu kelelahan mental dan berdampak pada performansi. Terdapat penurunan human reliability menjelang akhir jam kerja dan rata-rata mean time to human error dari seluruh partisipan adalah,155, 7 menit (2.59 jam) Dengan demikian maka strategi untuk mengoptimalkan performansi maka pegawai perlu beristirahat setelah 2.59 jam bekerja.